19 Using project ECHO to meet the demand for palliative care education and support across multiple settings. (13th October 2019) - Diffin, Janet; McTernaghan, Tracey; McMullan, Aine; Hayes, Martin; Watson, Max
Abstract : Background: Despite increasing demand, limited resources are often available to deliver high quality palliative care education. Project ECHO is a tele-mentoring programme that could address this disparity by using video-conferencing to deliver (i) best practice guidance and education from specialists, and (ii) case-based learning with peer discussion1. Five ECHO networks in Northern Ireland delivered palliative care education and support (Cardiology/Heart Failure, District nurses, Community pharmacy, Paediatrics, Marie Curie registered nurses). Participants set the curriculum and network aims and objectives, which included increasing participant's palliative care knowledge and skills, enhancing confidence, improving collaboration, and facilitating peer support. 45 ECHO sessions were delivered across five networks with 194 participants attending ≥2. Aim: Identify if each ECHO network achieved it aims and objectives. Methods: Retrospective online survey designed for each network administered after final ECHO session. Results: 27% (60/224) registered participants across each network responded. Overall, each network achieved its aims and objectives with participants reporting increased palliative care knowledge and increased confidence in managing end of life care scenarios. Benefits included case-based learning, professional networking, and avoidance of travel to access education. Participants reported improved communication with patients and families, and improved decision making in relation to patient care. Time restraints due to staffing issues or workload were identified as barriers to participation. Conclusion: Project ECHO may be an ideal solution for meeting the demand for palliative care education across multiple settings. To ensure practitioners fully benefit, protected time for participation is recommended. Funders: Health and Social Care Board/Hospice UK.